Adopting Design Thinking in Novice Multidisciplinary Teams: The Application and Limits of Design Methods and Reflexive Practices1. (4th October 2013) - Seidel, Victor P.; Fixson, Sebastian K.
Abstract : Scholarly and practitioner literature have both described the potential benefits of using methods associated with a "design thinking" approach to develop new innovations. Most studies of the main design thinking methods—needfinding, brainstorming, and prototyping—are based either on analyses of experienced designers or examine each method in isolation. If design thinking is to be widely adopted, less‐experienced users will employ these methods together, but we know little about their effect when newly adopted. Drawing on perspectives that consider concept development as broadly consisting of a divergent concept generation phase followed by a convergent concept selection phase, we collected data on 14 cases of novice multidisciplinary product development teams using design methods across both phases. Our hybrid qualitative and quantitative analysis indicate both benefits and limits of formal design methods: First, formal design methods were helpful not only during concept generation, but also during concept selection. Second, while brainstorming was valuable when combined with other methods, increased numbers of brainstorming sessions actually corresponded to lower performance, except in the setting where new members may join a team. And third, increased team reflexivity—such as from debating ideas, processes, or changes to concepts—was associated with more successful outcomes during concept generation but less successful outcomes during concept selection. We develop propositions related to the contingent use of brainstorming and team reflexivity depending on team composition and phase of development. Implications from this study include that novice multidisciplinary teams are more likely to be successful in applying design thinking when they can be guided to combine methods, are aware of the limits of brainstorming, and can transition from more‐ to less‐reflexive practices.